Using rush hour and daytime exposure indicators to estimate the short-term mortality effects of air pollution: A case study in the Sichuan Basin, China. (November 2018) - Guo, Bing; Chen, Fei; Deng, Ying; Zhang, Hongliang; Qiao, Xue; Qiao, Zhijiao; Ji, Kui; Zeng, Jing; Luo, Bin; Zhang, Wei; Zhang, Yuqin; Zhao, Xing
Abstract: Background: Daily mean concentrations of air pollutants have been widely used as exposure indicators to estimate the short-term mortality effects of outdoor air pollution. However, daily mean concentrations might insufficiently represent the true exposure level because of the diurnal variations of air pollutants and various human activity patterns. Daytime or rush-hour concentrations may lead to better estimations. Objective: Our study aimed to imitate the true exposure level under assumptions about human activity patterns and to examine the short-term mortality effects of the exposure to air pollution during a) the morning-evening rush hours ( ME ), b) the morning-lunch-evening rush hours ( MLE ), and c) the whole daytime ( WDT ) in Chengdu, Sichuan Basin, China. Methods: We investigated the diurnal variations of PM2.5, SO2, and O3 and examined the associations between the three pollutants and nonaccidental mortality, cardiovascular mortality, respiratory mortality using generalized additive model. Three novel exposure indicators ( ME, MLE, and WDT ) were employed to imitate the most probable exposure levels. Relative change of excess risk (ER) was used to compare effects estimated from models with different exposure indicators. Results: In the relationship of PM2.5 and mortality, ERs estimated from the novel-indicator models decreased by 4.88%–11.89% in comparison with ERs from the daily-indicator models. All the three novel indicators of SO2 offered lower ERs of respiratory mortality than the daily indicator did. Significant associations were observed in O3 -nonaccidental mortality at lag0 in both winter and spring, and O3 -cardiovascular mortality at lag0 in winter. Overall, majority of effect estimates based on rush-hour or daytime indicators were lower than the estimates based on daily mean concentrations. Conclusion: The use of daily mean concentrations may bias exposure assessment and thus inflating effect estimates. This study highlights the importance of rush-hour and daytime exposure and provides alternative indicators for estimating acute effects of air pollution. Graphical abstract: Image 1 Highlights: This work provides alternative strategies in assessing air pollution exposure. First work on the mortality effect of rush hour and daytime air pollution exposure. The mortality effect may be overestimated with daily mean concentration. Abstract : Majority of effect estimates based on rush-hour or daytime indicators were lower than the estimates based on daily mean concentrations.